Association between Cataract Surgery and Age-Related Macular Degeneration: A Systematic Review and Meta-Analysis - Lihong Yang; Hongxun Li; Xinheng Zhao; Ye Pan (Journal of Ophthalmology)
Purpose. We performed a systematic review and meta-analysis to evaluate the association between cataract surgery and the development and progression of AMD. Methods. This meta-analysis was registered at PROSPERO (CRD42017077962). We conducted a systematic literature search in August 2020 in Embase and PubMed and included cohort studies, case-control studies, or randomized controlled trials (RCTs) if they examined the association between cataract surgery and AMD. Odds ratio (OR) was used as a measure of the association with a random effect model. The analysis was further stratified by factors that could affect the outcomes. Results. 15 studies were included in this study. In the overall analysis, cataract surgery was significantly associated with the incidence of late AMD (OR, 1.80; 95% CI, 1.26–2.56; P = 0.001), particularly geographic atrophy (OR, 3.20; 95% CI, 1.90–5.39; P ≤ 0.001). No significant associations were observed between cataract surgery and the incidence of early AMD. Subgroup analysis showed that the OR for incidence of early and late AMD was significantly higher for cataract surgery performed more than 5 years compared with less than 5 years. We also found an increased risk of progression of AMD after cataract surgery performed more than 5 years (OR, 1.97; 95% CI, 1.29–3.01; P = 0.002). Conclusions. Our results suggest that cataract surgery may be associated with an increased risk of late AMD development and AMD progression. In addition, increasing the follow-up time since cataract surgery may further increase the risk for the development and progression of AMD. In the future, prospective multicenter studies with well-designed RCTs are required to confirm our findings.